2019
DOI: 10.1097/md.0000000000015314
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting bead transarterial chemoembolization (TACE) vs conventional TACE in treating hepatocellular carcinoma patients with multiple conventional TACE treatments history

Abstract: This study aimed to compare the efficacy and safety of drug-eluting bead transarterial chemoembolization (DEB-TACE) vs conventional TACE (cTACE) in hepatocellular carcinoma (HCC) patients with multiple cTACE treatments history. Eighty-one HCC patients with multiple cTACE treatments history who underwent DEB-TACE (N = 42) and cTACE treatment (N = 39) were included in this retrospective cohort study and allocated to DEB-TACE and cTACE groups accordingly. Multiple cTACE treatments history was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…At the main endpoint of this study, we found that the median OS of the group with SARPS invasion was significantly longer than that of the group with RAPS invasion. In terms of secondary endpoints, overall, the ORR and DCR were only 48.9% and 63.4%, respectively, similar to the results described by Li et al (29), which may be related to the large tumors (n = 35, >5 cm), PV/HV branch invasion, and retroperitoneal invasion in the patients we included. However, the ORR and DCR were significantly higher in the group with SARPS invasion than in the group with RAPS invasion, which we believe that this finding may be related to the location and aggressiveness of the tumors, since there were no notable differences in baseline characteristics among patients with HCC with different areas of rRPS invasion, we believe that these data were justified.…”
Section: Discussionsupporting
confidence: 85%
“…At the main endpoint of this study, we found that the median OS of the group with SARPS invasion was significantly longer than that of the group with RAPS invasion. In terms of secondary endpoints, overall, the ORR and DCR were only 48.9% and 63.4%, respectively, similar to the results described by Li et al (29), which may be related to the large tumors (n = 35, >5 cm), PV/HV branch invasion, and retroperitoneal invasion in the patients we included. However, the ORR and DCR were significantly higher in the group with SARPS invasion than in the group with RAPS invasion, which we believe that this finding may be related to the location and aggressiveness of the tumors, since there were no notable differences in baseline characteristics among patients with HCC with different areas of rRPS invasion, we believe that these data were justified.…”
Section: Discussionsupporting
confidence: 85%
“… 30 Furthermore, a recent study with HCC patients (including patients with Child–Pugh A, 85.7% and Child–Pugh B, 14.3%) showed that DEB-TACE was effective in HCC patients with multiple c-TACE treatments history compared with continuous c-TACE treatments. 31 In this study, a large nodule (more than 7 cm) and advanced BCLC stage (C/D) were independent poor prognostic factors. 31 In the present study, although antitumor effect was independent of UT7 criteria, tumor size was relatively small (median 2.5 cm).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, we evaluated HCC status of the liver with "up-to-seven (UT7) criteria" 24 because intrahepatic tumor factors such as size and number of tumor are known to be associated with effectiveness of TACE and patients' survival after TACE. 25,26 Written informed consent was obtained from all participants before treatment, and this study was approved by our institutional ethics committee (Ethics Committee, University of Toyama, Approved Number: [25][26][27][28][29][30][31]. This study was conducted in accordance with the Declaration of Helsinki.…”
Section: Patients Selectionmentioning
confidence: 99%
“…This might also affect the treatment efficacy, as there are already studies elucidating a better efficacy of DEB compared with TACE using lipiodol and conventional embolic agents. [ 25 27 ] However, these studies are all conducted in liver cancer patients but not other malignancies, therefore, the effect of embolic agents (both DEB and conventional embolic agents) on efficiency and safety in patients with cancers other than liver cancer should be evaluated in future studies with larger sample size. Moreover, complementary embolization is used in some of our patients (most of who have large tumors), which is also a factor influencing the efficacy that should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%